AKTIVITAS SALEP EKSTRAK DAUN SEMBUNG RAMBAT (Mikania micrantha Kunth) SEBAGAI OBAT LUKA SAYAT PADA MENCIT - Santi Perawati; Lili Andriani; Salwa Winasti Erwin (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Ointment is a semisolid preparation that is soft, easy to apply, and is used as an external medicine on the skin and mucous membranes. Many researches related to preparations as wound medicine from natural ingredients have been carried out. One of the plants known to have medicinal properties is the sembung vine. This study aims to determine whether the extract and fraction of the leaves of sembung rambat can have the potential to treat cuts in male mice. This study aims to determine whether sembung rambat leaf extract ointment has the potential as a medicine for incisions in mice. the result is laboratory experimental study, where the activity of exracts and preparations of sembung rambat leaf oinmment as a wound medicine in male mice will be tasted using the maceration method, liquid-liquid extraction then this study measures the length of the wound on the first day, and the last day of treatment then the measurement result are analyzed and compared with each treatment group. The results showed that the extract with a concentration of 8% had the fastest cure rate in mice. Therefore, it can be concluded that sembung rambat leaf extract ointment has activity as an incision medicine in mice.